Epitope mapping and kinetics of CD4 T cell immunity to pneumonia virus of mice in the C57BL/6 strain - Vandersarren, Lana; Bosteels, Cedric; Vanheerswynghels, Manon; Moon, James J.; Easton, Andrew J.; Van Isterdael, Gert; Janssens, Sophie; Lambrecht, Bart N.; van Helden, Mary J. (Scientific reports, 2017)
Pneumonia virus of mice (PVM) infection has been widely used as a rodent model to study the closely related human respiratory syncytial virus (hRSV). While T cells are indispensable for viral clearance, they also contribute to immunopathology. To gain more insight into mechanistic details, novel tools are needed that allow to study virus-specific T cells in C57BL/6 mice as the majority of transgenic mice are only available on this background. While PVM-specific CD8 T cell epitopes were recently described, so far no PVM-specific CD4 T cell epitopes have been identified within the C57BL/6 strain. Therefore, we set out to map H2-IA b -restricted epitopes along the PVM proteome. By means of in silico prediction and subsequent functional validation, we were able to identify a MHCII-restricted CD4 T cell epitope, corresponding to amino acids 37–47 in the PVM matrix protein (M 37–47 ). Using this newly identified MHCII-restricted M 37–47 epitope and a previously described MHCI-restricted N 339–347 epitope, we generated peptide-loaded MHCII and MHCI tetramers and characterized the dynamics of virus-specific CD4 and CD8 T cell responses in vivo . The findings of this study can provide a basis for detailed investigation of T cell-mediated immune responses to PVM in a variety of genetically modified C57BL/6 mice.